Python-Based Linear Regression Modeling of Liquidity and Profitability Ratios as Determinants of Firm Value in Commercial Banks in Indonesia - Febriyanti, Zahra; Karismariyanti, Magdalena; Sukmawati, Fitri (Politeknik Negeri Batam, 2025)
The decline in Indonesian banking stocks in early 2024 was caused by foreign capital outflows. A decrease in foreign investment can reduce banks' ability to maintain their capital structure and intensify liquidity pressures. The primary measure for assessing company value is firm value, which can attract investors and indicate potential returns for shareholders. This study aims to analyze the influence of liquidity and profitability on firm value. The sample consists of 55 firm-year observations from the banking sector listed on the Indonesia Stock Exchange (IDX) ranging from 2019 to 2023, obtained using a purposive sampling technique. Data processed with Python using Multiple Linear Regression shows that liquidity has a significant and positive effect on firm value. Similarly, profitability also has a positive and significant effect on firm value. The results of the F-test indicate that liquidity and profitability have a simultaneous influence on firm value. The model demonstrates an outstanding prediction rate, with an R-squared value of 99.8%. The model These findings contribute valuable insights for stakeholders and investors, suggesting that by assessing the strength of liquidity and profitability in financial statements, they can enhance their profit potential.